ミクログリアにおけるミトコンドリア機能不全が炎症誘発性I型インターフェロン発現に及ぼす影響 - 中村, 庸輝; 岩本, 桃香; 中島, 一恵; 森岡, 徳光 (日本薬理学会年会要旨集, 2021)
Background: Inflammation in central nerve system (CNS) is involved in onset and exacerbation of neurodegenerative diseases. Microglia are known to play an important role in the CNS as main immune cells. Recent investigations demonstrated that mitochondrial function is impaired in the brains of aged people and patients with neurodegenerative diseases. However, whether mitochondria dysfunction affect microglial immune responses remains unclear. Therefore, the current study has investigated the involvement of mitochondrial dysfunction in the lipopolysaccharide (LPS)-induced immune responses in microglia.Method: BV2 cells, a mouse microglial cell line, were treated by rotenone, an electron transporter chain I inhibitor, for 24 hours to impair the mitochondrial function. Expression levels of mRNA were measured by the real-time PCR.Results: Treatment of BV2 cells with rotenone significantly upregulated the LPS-induced mRNA expression of interferon (IFN)-β, but not IFN-α. On the other hand, rotenone treatment did not enhance LPS-induced pro-inflammatory cytokines such as interleukin (IL)-1β, IL-6 and tumor necrosis factor-α.Conclusions: The current study indicates that mitochondrial dysfunction in microglia modulates the inflammatory response in particular induction of IFN-β.